The Challenges of Measuring and Valuing Quality of Life in Preschool Children: A Retrospective Review of NICE Appraisals - Alan Lamb; Alice Murray; Rosie Lovett (MDPI AG, 2021)
Health technology assessment agencies evaluate interventions across the lifespan. However, there is no consensus about best-practice methods to measure health-related quality of life (HRQoL) in preschool children (<5 years) and data are often scarce. We reviewed methods used to capture the HRQoL of preschool children in past National Institute for Health and Care Excellence (NICE) appraisals to establish whether there is a need for better methods in this area and if so, to identify priority research areas. We identified past NICE appraisals that included preschool children, examining the methods used to generate utility values and whether committees believed these captured HRQoL adequately. Of the 12 appraisals, most used generic HRQoL measures designed for adults. Measures were usually completed by adult patients or clinical experts. Committees frequently commented on limitations in the HRQoL data. While acknowledging that data collection may be challenging, committees would value evidence based on HRQoL data from parents or guardians collected as part of a clinical trial. We identified several research priorities including the psychometric properties of existing measures; the feasibility and validity of valuation studies; and mapping. Progress in these areas will help ensure that the aspects of HRQoL which matter to children and their families are captured in NICE evaluations.